(untitled) (Pedagogy of Higher and Secondary Education, 2015)
Bondarenko A. V. Polish researchers about musical and aesthetic development of comprehensive schools students. In the given article the author shows the problem of musical and aesthetic development of comprehensive schools students in Poland. The questions of music abilities development and children’s creative development by means of music are highlighted in the article. The article deals with different aspects of the educational work of music teachers taking into account the modern priorities of education.